PEMBANGUNAN HUKUM PERLINDUNGAN NELAYAN TRADISIONAL DI ACEH DALAM KAITAN PEMANFAATAN SUMBER DAYA PERIKANAN SECARA BERKEADILAN - Sulaiman, Sulaiman; Adli Abdullah, Muhammad; Muttaqin Mansur, Teuku; Zulfan, Zulfan (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
Traditional fishermen feel the impact of the damage of marine ecosystems and fisheries. The damage is not only caused by the consumption aspect, but also due to the government policy. Although it has great potential, but most of the traditional fishing communities are poor. This study seeks to answer three questions, namely: how to protect traditional fishermen in Aceh in connection with the consumption of fishery resources? What factors cause justice to be important in the context of the protection of traditional fishermen? How does the development of the law is supposed to do to protect traditional fishing? This study examines the law in non-doctrinal perspective with socio-legal approach. The third source of information is the Bureau of Maritime Affairs and Fisheries, FAO staff, the community of fishermen, fishery-environmental NGOs, and academics marine, fisheries, and the customary law of the sea. Protection of traditional fishermen is very important undertaken by the country in the consumption of fishery resources due to the presence of traditional fishermen in exploiting fisheries resources not only as an economic activity, but also related to culture. Fairness factor in the protection of traditional fishermen need to be explored to remember a few things, namely poverty, access, utilization, ease of access to markets, and access management. Development protection laws in connection with the issue of fishermen should be the most important principle, which is to bring the state in providing basic rights as outlined in the Constitution. Access restrictions or lack of interest will basically lead a traditional fishing in marginal conditions either political, social, cultural, or economic. This study suggests that in order to restore the traditional fishermen, it is important to conduct study on the various legislations, ranging from legal to technical regulations, to find a map of the position of traditional fishermen in Indonesia. Based on these maps, traditional fishing is authorized with the participation of various sectors of the program provided for the fishing communities.